A Sustainable Revolution Let's Go Sustainable to Get our Globe Cleaner - D'Adamo, Idiano; Falcone, Pasquale Marcello; Martin, Michael; Rosa, Paolo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The parties of the United Nations Framework Convention on Climate Change (UNFCCC) attained the Paris Agreement to tackle climate change and to strengthen the actions required for a sustainable transition towards an environmentally friendly future. This transition will involve holistic approaches and multifaceted societal shifts, requiring answers and collaboration between private, public, and academic sectors. This book gathers together contributions which study the transition towards a more sustainable future, involving and identifying the development and implications of more sustainable alternatives, in collaboration with all relevant stakeholders (e.g. communities, firms, policy makers, researchers, etc.), to achieve this transition. The approaches proposed are all concerned with a common perspective: imaging our globe with a greener picture, built upon a transversal sustainable revolution to clean up the Earth.